SPEECH ACT OF ILTIFAT AND ITS INDONESIAN TRANSLATION PROBLEMS - Al Farisi, Zaka (Indonesian Journal of Applied Linguistics, 2015)
Abstract: Iltifat (shifting) speech act is distinctive and considered unique style of Arabic. It has potential errors when it is translated into Indonesian. Therefore, translation of iltifat speech act into another language can be an important issue. The objective of the study is to know translation procedures/techniques and ideology required in dealing with iltifat speech act. This research is directed at translation as a cognitive product of a translator. The data used in the present study were the corpus of Koranic verses that contain iltifat speech act along with their translation. Data analysis typically used descriptive-evaluative method with content analysis model. The data source of this research consisted of the Koran and its translation. The purposive sampling technique was employed, with the sample of the iltifat speech act contained in the Koran. The results showed that more than 60% of iltifat speech act were translated by using literal procedure. The significant number of literal translation of the verses asserts that the Ministry of Religious Affairs tended to use literal method of translation. In other words, the Koran translation made by the Ministry of Religious Affairs tended to be oriented to the source language in dealing with iltifat speech act. The number of the literal procedure used shows a tendency of foreignization ideology. Transitional pronouns contained in the iltifat speech act can be clearly translated when thick translations were used in the form of description in parentheses. In this case, explanation can be a choice in translating iltifat speech act.